THE EFFECT OF THE FLIPPED CLASSROOM LEARNING MODEL ON THE INDEPENDENT LEARNING OF STUDENTS OF CLASS X ACCOUNTING AT SMK NEGERI 48 JAKARTA DURING THE COVID-19 PANDEMIC - Eli Rahayu Setyaningsih; Mardi Mardi; Santi Susanti (International Journal of Multidisciplinary Research and Literature, 2022)
This study aims to determine the effect of the Flipped Classroom learning model on the learning independence of class X Accounting students at SMK Negeri 48 Jakarta during the Covid-19 Pandemic Period. This research uses a quantitative approach with a quasi-experimental quasi-experimental method, and the research design uses a Posttest Only Control Group Design. The subjects in this study were students of class X Accounting 1 and 2, with 72 students. The sampling technique used is the purposive sampling technique. The data collection technique used a questionnaire instrument for student learning independence. Calculate the validity of the statement items using the product-moment formula and reliability using the Cronbach Alfa formula. The data analysis technique was carried out with prerequisite tests, first with normality test using Liliefors test and homogeneity using Fisher's exact test. Then test the hypothesis by using the t-test. The results of the requirements analysis test stated that in the normality test, the two classes were normally distributed. The results of the homogeneity test of the variance data were homogeneous. Hypothesis testing using SPSS.v26 shows that a p-value of 0.020 is obtained with a significance of 0.05. Thus, p-value < t table (0.020 < 0.05), so Ho is rejected and Ha is accepted, which means there is a significant influence in the Flipped Classroom learning model with the help of video learning on student learning independence in Basic Accounting Subjects for class X Accounting at SMK Negeri 48 Jakarta during the Covid-19 pandemic